Utilization of Instructional Materials and Effective Teaching and Learning of English Language in Early Childhood Schools - Magdalene I. Ogbemudia; Victor M. Alasa; Esther C. Wordu (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This study examined the effect of utilization of instructional materials on effective teaching and learning of English Language in Early Childhood Schools in Uyo Local Government Area, Akwa Ibom State of Nigeria. Three research questions and three hypotheses were formulated to guide the study. The descriptive survey research design was used for the study. A sample size of 300 kindergartens three (KG, 3) pupils was selected using simple random sampling technique. “Utilization of Instructional Materials and Effective Teaching and Learning of English Language in Early Childhood Schools Questionnaire (UIMETLELECSQ)” was used for data collection. The instrument was face validated. A reliability coefficient of 0.86 was obtained for the instrument using Cronbach Alpha. Mean and standard deviation were used to answer the research questions while Chi-square (X2) test was used to test the hypotheses at .05 level of significance. The findings of the study indicated that visual materials, audio materials and audio-visual materials significantly influenced the effective teaching and learning of English Language in Early Childhood Schools. It was recommended among others that professional bodies and private individuals should strive to complement government efforts in providing necessary instructional materials to Early the Childhood Schools so as to enhance the teaching effectiveness of teachers of English Language.